Considering the major mental disorders as clinical expressions of periodic pathological oscillations of the overall operating mode of brain function - Pediaditakis, Nicholas (Medical hypotheses, 2006)
The consideration of the collective significance of the shared characteristics and overlaps in the clinical expression and pharmacological responses of the major mental disorders (namely, schizophrenia, bipolar disorders, obsessive compulsive disorder, anxieties/phobias, borderline syndrome and possibly others) supports the following: (1) These disorders have a common, initial neurodevelopmental origin. (2) They occur probabilistically on some of “at-risk” individuals whose pre-existing, extreme, temperamental/structural variance confers vulnerability for such occurrence. (3) Lastly, each of these syndromes can be considered as a clinical expression of oscillations (i.e., a switch to a pathologically ordered phase) of the overall, common operating mode of brain function. This mode based on a particular-for-our-brain, emergent quality of complexity, normally ensures the synchrony, coordination, subtlety and robust flexibility in the expression of the components of each of the various higher faculties of the brain, namely, the faculty of: (1) mood modulation; (2) coordination of feelings, thoughts and the responses to the external world; and (3) keeping constrain and limited but appropriate input of primitive drives. The conclusions in this paper have important ramifications in rethinking the current nosological procrustean flawed classification and the neurodevelopmental origin of the major mental disorders as well as the biases shown in selecting subjects for research. It also opens opportunities in the future development of novel, effective, economical and harmless therapies that will restore and maintain the normal phase of the operating mode of brain function. For example, the patient can wear an appropriate electronic device that sends a particular type of signal to the brain which will affect remission and prevent relapses without harm. We can thus avoid the use of pharmacological agents which have limited effectiveness, severe, long-term side-effects and financial burden to the patient.